Progettare "paesaggi di limite - Antonella Valentini (Scuole di dottorato, 2005)
This book addresses the issue of the design of urban fringe landscapes, focusing in particular on the experience of the "green belts" and the "green wedges". Experimenting in the urban peripheries of Florence, the fringe landscape project is not aimed at the reconstruction of ideal city limits, but is a container for examples of rebalance, connotation and regeneration proper to the border areas, which feature an indeterminacy of identifying characteristics and a marked reduction in landscape quality.